2023
DOI: 10.1093/ecco-jcc/jjac190.0540
|View full text |Cite
|
Sign up to set email alerts
|

P410 Long-term persistence and safety of biological drugs in patients with Inflammatory Bowel Disease. Differences between women and men: SEXEII study of ENEIDA

Abstract: Background Female sex has been associated with a worse response to anti-TNF drugs and with discontinuation of these drugs in immune-mediated diseases. Data in Inflammatory Bowel Disease (IBD) are unclear. The aims of study are to assess possible differences in long-term treatment persistence and safety of biological drugs between women and men with IBD. Methods Multicenter observational study carried out with data from the EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a result, patients with CD are more likely to develop stricturing and penetrating phenotypes, have a higher likelihood of developing extraintestinal manifestations, and, 10 years into their disease course, ~40–60% of CD patients will require surgical resection as compared to a lifetime colectomy risk in UC of ~10–15%. 2–4 Nonetheless, large epidemiological studies have identified that some patients with CD will experience a more indolent course and accurately differentiating those patients with progressively bowel-damaging CD from those with non-progressive phenotypes is a research priority. 5 Despite these important differences between CD and UC, treatment strategies aimed at escalating to advanced therapies early in the disease course, commonly defined as ‘window of opportunity’ within 2–3 years of diagnosis, are often adapted from management of CD to that of UC.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, patients with CD are more likely to develop stricturing and penetrating phenotypes, have a higher likelihood of developing extraintestinal manifestations, and, 10 years into their disease course, ~40–60% of CD patients will require surgical resection as compared to a lifetime colectomy risk in UC of ~10–15%. 2–4 Nonetheless, large epidemiological studies have identified that some patients with CD will experience a more indolent course and accurately differentiating those patients with progressively bowel-damaging CD from those with non-progressive phenotypes is a research priority. 5 Despite these important differences between CD and UC, treatment strategies aimed at escalating to advanced therapies early in the disease course, commonly defined as ‘window of opportunity’ within 2–3 years of diagnosis, are often adapted from management of CD to that of UC.…”
Section: Introductionmentioning
confidence: 99%